DEVELOPMENT STRATEGY OF MANGROVE ECOTOURISM IN TELUK PAMBANG VILLAGE BANTAN DISTRICT BENGKALIS REGENCY - Muhammad Rudy Hidayat; Defri Yoza; Viny Volcherina Darlis (Jurnal Ilmu Ilmu Kehutanan, 2021)
Mangrove forests have an important role in regulating the stability of sea and land conditions, as well as forming various species of trees, shrubs and flora. One area that has a mangrove ecosystem in Bengkalis Regency is Teluk Pambang Village. Mangrove ecotourism in Teluk Pambang has good potential to be developed such as natural resources, characteristics and uniqueness of mangroves, diversity of mangrove species and regional comfort. The aims of this research are (1) know the potential and attractiveness of mangrove ecotourism and (2) determine the strategy of developing mangrove ecotourism in Teluk Pambang Village, Bantan Regency, Bengkalis Regency. This research began in December 2018 in the village of Teluk Pambang, Bantan Regency, Bengkalis Regency. The study was conducted using methods of field observation, observation and study of literature. Analysis of the ecotourism development strategy was carried out in the SWOT analysis. The potential of mangrove forest ecotourism in Teluk Pambang has beautiful natural scenery, a high level of security, and there are 10 species of fauna and 9 species of flora. Based on differences in the number of internal and external factors, the Strategy Matrix is in quadrant 1. Strategies to develop mangrove forest ecotourism, namely increasing human resources (HR), planting rare mangrove species, planting mangrove abrasion barriers, development, procurement of facilities and supporting infrastructure so both among the stakeholders.